Life-threatening complications in patients with thoracic and abdominal lymphatic malformations - Prytula, V. P.; Rudenko, Y. O.; Gorbatiuk, O. M.; Nakonechnyi, A. Y.; Susak, Y. M. (General Surgery, 2023)
The term «lymphatic malformations» (LMs) refers to a wide spectrum of disorders with clinical manifestations that can vary from asymptomatic to life‑threatening. Objective — to analyze the factors and pathological conditions that necessitate the use of emergency surgical procedures in patients with thoracic and abdominal LMs. Materials and methods. The retrospective study of medical charts of patients with LMs was performed for a period from 2012 to 2021. Among 240 patients with LMs, 55 (22.9%) were diagnosed with lesions of the abdominal or thoracic cavity. 5 (9.1%) required an emergency surgical procedure. Results. Among 38 patients with abdominal LMs, only one (2.6%) required emergency surgery. This patient underwent laparotomy and subtotal bowel resection for total mesenteric thrombosis. The postoperative period was complicated by short bowel syndrome. Mediastinal LMs were diagnosed in 17 patients, 14 (73.7%) of whom had neck LM extension. In 4 cases, mediastinal LMs were complicated by intrathoracic tension syndrome. It was caused by a lymphatic leak into the pleural cavity in 1 case and by sudden enlargement of LMs, resulting from intracystic hemorrhage, in 3 other cases. A pleural drain with subsequent sclerotherapy was used in a patient with chylothorax. Patients with intracystic hemorrhage underwent thoracotomy and partial LM resection. They also received an injection of a sclerosing agent into the residual cysts. In uncomplicated cases, minimally invasive methods were preferred, with laparoscopic resections of abdominal LMs in 22 (78.6%) patients and sclerotherapy under ultrasound guidance in 7 (36.8%) patients with mediastinal LMs. Conclusions. Intrathoracic tension syndrome and thrombotic complications are potentially dangerous and life‑threatening conditions that pose a risk to patients with visceral LMs and require emergency interventions. Minimally invasive technologies were preferred in uncomplicated cases of thoracic and abdominal LMs, whereas open surgeries were the method of choice in complicated cases.